2016
DOI: 10.1016/j.jmaa.2015.12.049
|View full text |Cite
|
Sign up to set email alerts
|

On stabilization of small solutions in the nonlinear Dirac equation with a trapping potential

Abstract: We consider a Dirac operator with short range potential and with eigenvalues. We add a nonlinear term and we show that the small standing waves of the corresponding nonlinear Dirac equation (NLD) are attractors for small solutions of the NLD. This extends to the NLD results already known for the Nonlinear Schrödinger Equation (NLS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…These assumptions are verified in some perturbative context with V = 0. This case is analyzed in [45]. The asymptotic stability approach from [17,40,127] is developed under important restrictions on the types of admissible perturbations.…”
Section: Orbital and Asymptotic Stability Of Solitary Wavesmentioning
confidence: 99%
“…These assumptions are verified in some perturbative context with V = 0. This case is analyzed in [45]. The asymptotic stability approach from [17,40,127] is developed under important restrictions on the types of admissible perturbations.…”
Section: Orbital and Asymptotic Stability Of Solitary Wavesmentioning
confidence: 99%
“…As discussed in [9], the approach in [32] involving guesses on the trajectory of a solution, the turns of the solution away from unstable standing waves and, usually, its final convergence either to 0 or to a stable standing wave, appears a considerably difficult task under our hypothesis (H2), which is much more complex combinatorially than the situation in [32]. In this paper we frame the problem as in [9] and extend to the NLKG equation the NLS result obtained in [9], exactly as in [11] the result of [9] has been extended to Dirac equations. It turns out that the NLKG presents no significant new problems with respect to the NLS.…”
Section: Introductionmentioning
confidence: 96%
“…Such invariant spaces exist near the origin also for the nonlinear problem (1.1) in the form of topological disks which are tangent to the linear spaces at the origin. In the case of the nonlinear Schrödinger equation, [9], and of the nonlinear Dirac equation, [11], it as been shown that the union of these disks is an attractor for all small energy solutions. We will prove the same result for (1.1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us mention the results on convergence of small solutions to (one-frequency) solitary waves, particularly in the context of the nonlinear Schrödinger equation: in other words, the attractor of small solutions is formed by small amplitude solitary waves. See in particular [TY02,SW04,CM15,CMP16,CT16].…”
Section: Introductionmentioning
confidence: 99%